A sociocultural approach to communication instruction: How insights from communication teaching practices can inform faculty development programs. Issue 4 (20th October 2021) - Hora, Matthew T.; Benbow, Ross J.; Lee, Changhee
ABSTRACT: Background: Postsecondary institutions are expected to provide students with skills such as communication that are considered essential for success in school, work, and society. However, faculty are rarely trained to design courses that emphasize complex, cultural skills like communication, highlighting the need for professional development that adopts a sociocultural perspective on skills, teaching and faculty learning. Methods: In this paper, we describe a mixed-methods study that aimed to document instructional practice based on decision-making interviews (n=25), classroom observations (n=20) and surveys (n=496) with faculty in two U.S. cities. Techniques used to analyze these data include inductive thematic analysis, social network analysis, and hierarchical linear modeling. Findings: Results of the analysis include the identification of key elements of course planning – faculty predispositions, perceived affordances, and instructional goals—which dynamically interact to inform teaching practices. Classroom observations revealed a range of methods from lecturing to classroom debates. Results also highlight three factors that led to teaching decisions: prior experience in industry which sensitized faculty to employer needs, social networks, and student skills. Contributions: The data contribute to research on skills-focused instruction, and we conclude the paper with a description of a socioculturally informed faculty development program based on study findings.